Análise de desempenho na rede metropolitana de saúde da Universidade Federal do Rio Grande do Norte : um dimensionamento aplicado a telemedicina e a telessaúde utilizando QoS baseado no padrão IEEE 802.1Q - Medeiros, Ronaldo Maia de (2014)
It s notorious the advance of computer networks in recent decades, whether in relation to transmission rates, the number of interconnected devices or the existing applications. In parallel, it s also visible this progress in various sectors of the automation, such as: industrial, commercial and residential. In one of its branches, we find the hospital networks, which can make the use of a range of services, ranging from the simple registration of patients to a surgery by a robot under the supervision of a physician. In the context of both worlds, appear the applications in Telemedicine and Telehealth, which work with the transfer in real time of high resolution images, sound, video and patient data. Then comes a problem, since the computer networks, originally developed for the transfer of less complex data, is now being used by a service that involves high transfer rates and needs requirements for quality of service (QoS) offered by the network . Thus, this work aims to do the analysis and comparison of performance of a network when subjected to this type of application, for two different situations: the first without the use of QoS policies, and the second with the application of such policies, using as scenario for testing, the Metropolitan Health Network of the Federal University of Rio Grande do Norte (UFRN)